The Relationship between Knowledge and Community Stigma Against Covid-19 Sufferers in Tasikmalaya - Bayu Brahmantia; Miftahul Falah; Nina Pamela Sari; Lilis Lismayanti; Sri Wahyuni (Fakultas Kedokteran, Universitas Mulawarman, 2023)
Background: Covid-19 Is A Disease That Can Be Transmitted Through Lifestyle. Knowledge Is A Person's Information About A Subject Obtained From An Experience Gained During Education Or From His Own Experience. A stigma is an event that occurs in an individual by being labeled, stereotyped, separated, and partially subject to discrimination. Purpose: To Know The Relationship Of Knowledge With Community Stigma Toward Covid-19 Sufferers In Cipedes Village. Methods: The analytical survey method with a cross-sectional study approach. There were 361 respondents. Results: This research was conducted using the Chi-Square test. The results showed that 50 respondents with less Knowledge (13.9%) and stigma were in a positive category, nine respondents with less Knowledge (2.5%) and negative Stigma, nine respondents with sufficient Knowledge 96 people (26.6%) and stigma in the positive category, 44 people (12.2%) with sufficient Knowledge and Stigma in the harmful category, 92 respondents with good Knowledge (25.5%) and Stigma in the harmful category Positive, Respondents with Good Knowledge Category, namely 70 people (19.4%) and Stigma in the Negative Category, in a P value = 0.000 (<0.05), Conclusion: It can be concluded that there is a relationship between Knowledge and Community Stigma for Covid Sufferers -19 In Cipedes Village. Researchers suggest that health agencies, especially nursing, carry out promotional efforts by conducting health education regarding Covid-19 and Stigma, as well as for people to care more about people who suffer from Covid-19, both sufferers and survivors so that people affected by Covid-19 have high motivation. Make Sufferer's Immunity Increase.